Tow years evaluation of Effectiveness of caries preventive precisures - Pourhashemi SJ; Nabaei B (Tehran University of Medical Sciences, 1999)
The purpose of this survey was the determine of effectiveness of preventive precisures. 320 twelve years school student have chosen randomly. After determination of DMFT All of them divided to 4 groups. First group as control and the other groups were as oral hygiene education 6-fluoride therapy and sealant therapy group in a period of two years."nResults of this study showed that fluoride therapy was more effective than the other procisures than oral hygiene instructions.